Analisa Biaya Pengobatan Demam Tifoid Berdasarkan Clinical Pathway Di Rumah Sakit Harapan Bunda - Pieter Hazmen; Shirly Kumala; Prih Sarnianto (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2019)
Clinical pathways are used in quality and cost control with indicators of length of stay. Cases of typhoid fever at Harapan Bunda Hospital include the criteria for the first rank of High Volume in 2018 and Problem Prone in the cost of treatment. The purpose of the study is to analyze the cost of treatment based on the implementation of clinical pathways in antibiotic therapy. Observational research with comparative studies of the use of injection antibiotics based on clinical pathway implementation. Retrospective data collection with dependent outcome therapy variables (cost and length of stay) while the independent variable regimen of antibiotic use. The population of typhoid fever patients according to the criteria for the implementation of clinical pathway ICD code (A0.10) 571 patients. Samples using total sampling that fulfills the criteria of direct inclusion are made into samples divided by the antibiotic regimen of the payment system, the group with the least amount excluded. There were 4 observation groups: generic ceftriaxone (n = 52) branded ceftriaxone (n = 51), generic cefotaxime (n = 53) and branded cefotaxime (n = 57) totaling 213 patients. Satatistic test results of length of stay (p> 0.05) explained that they did not have a significant difference, the average value (5.1596). Medical expenses for generic cefotaxime (Rp 4,072,002,6792), generic cherryax (Rp 4,479,480,4808), branded cefotaxime (Rp 6,945,258,3333) and branded ceftriaxone (Rp 7,296,933,5686). Conclusions based on JKN (AMiB) antibiotic payment systems are cheaper than general and the cheapest cefotaxime cheapest generic antibiotics.